Oxygen-deficient nano-material, solid-phase melting zinc thermal reduction preparation method and application of oxygen-deficient nano-material

Through solid-phase melted zinc thermal reduction technology, oxygen defect nanomaterials with adjustable oxygen defect concentrations were successfully prepared, which solved the problems of complex preparation processes and high safety risks in the existing technology, achieved an efficient and simple preparation process, and significantly improved the cycle life of zinc ion batteries.

CN119612585AActive Publication Date: 2025-03-14YANGZHOU UNIV

Patent Information

Application Number
CN202411739702.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-14
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The existing oxygen-deficient nanomaterial preparation technology has problems such as difficulty in introducing controllable defects, difficulty in supplying large scale, complex preparation process and high safety risks.

Method used

Using solid-phase molten zinc thermal reduction technology, oxygen defect nanomaterials with adjustable oxygen defect concentrations are prepared by mixing transition metal oxide nanomaterials with zinc powder, ball milling, annealing and acid/base washing.

Benefits of technology

It realizes efficient, simple and universal preparation of oxygen-deficient nanomaterials, has good processing safety and industrial compatibility, and can effectively improve the cycle life of zinc ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612585A_ABST
    Figure CN119612585A_ABST
Patent Text Reader

Abstract

The invention relates to an oxygen-deficient nano material and a solid-phase melting zinc thermal reduction preparation method and application thereof, zinc powder is taken as a reducing agent, target metal oxide such as anatase type TiO2 and zinc powder are uniformly mixed, then mild high-temperature annealing treatment is carried out in an inert gas atmosphere, a product is washed by dilute acid / alkali, and the oxygen-deficient TiO2-x nano material is obtained. Similarly, oxygen deficient SnO2-x, ZrO2-x, and BaTiO3-x materials can be produced by such methods. Compared with the existing technologies of high-temperature hydrogen reduction, complex structure carbonization, solvothermal reduction and the like for preparing the oxygen-deficient nano material, the preparation method disclosed by the invention adopts a solid-phase molten zinc thermal reduction technology, takes environment-friendly and low-cost zinc powder as a reducing agent, and prepares the oxygen-deficient nano material by utilizing a solid-phase molten zinc thermal reduction process at a mild high temperature; the preparation method has the advantages of simple process, no special requirement on production equipment, processing universality and industrial production compatibility, successfully prepares a series of defect nanometer materials with adjustable oxygen defect concentration, and effectively prolongs the cycle life of the zinc battery by applying the defect nanometer materials to the negative electrode protection of the zinc ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of oxygen-deficient nanomaterials, and in particular to an oxygen-deficient nanomaterial, a solid-phase molten zinc thermal reduction preparation method and application thereof. Background Art

[0002] In recent years, renewable energy technologies such as wind power and photovoltaic power have developed rapidly. However, the distribution of these renewable energy sources is mostly limited by factors such as geographical location and seasonal time, and they urgently need to be equipped with efficient and new energy storage technologies to achieve their effective output and utilization.

[0003] With its advantages of high energy density, high energy conversion efficiency, and no memory effect, lithium-ion battery technology is widely used in portable electronic devices and new energy vehicles. However, after deep cycling, lithium batteries are prone to lithium precipitation at the graphite negative electrode when overcharged, and dendrites pierce the diaphragm to cause internal short circuits. At the same time, due to its high sensitivity to water vapor, lithium batteries use organic electrolytes, which are prone to electrolyte decomposition and gas production. Lithium dendrites further aggravate the above phenomenon, generate a lot of heat and cause serious safety accidents such as fire and explosion. In recent years, lithium battery electric vehicles have caught fire and exploded frequently, and their safety challenges are severe. On the other hand, the global land lithium resource reserves are limited and extremely unevenly distributed. The technical requirements and costs of lithium resource mining are high, resulting in high costs for battery-grade lithium carbonate. Therefore, the development of new and efficient energy storage technologies is of great scientific significance and application value.

[0004] Aqueous zinc-ion batteries have high volumetric energy density and operational safety (no fire risk), and are a highly promising large-scale energy storage technology. Due to its water stability, low electrode potential and high hydrogen evolution barrier, zinc metal is used as the negative electrode material for many zinc-based battery technologies. However, in aqueous electrolytes, zinc metal negative electrodes face severe challenges such as dendrite growth, hydrogen evolution side reactions and interfacial byproduct deposition. Many oxide nanomaterials are used for zinc negative electrode interface modification, and oxygen-deficient nanomaterials can further reduce the zinc deposition barrier and improve its cycle life. However, the preparation of oxygen-deficient materials is currently mainly based on high-temperature hydrogen reduction, complex structure carbonization, solvent thermal reduction and other technologies. The controllable introduction of defects and large-scale supply are difficult, the preparation process is complex and has safety risks. Therefore, the development of efficient, universal and scalable oxygen-deficient nanomaterial preparation technology has important scientific significance, broad application prospects and economic value. Summary of the invention

[0005] Technical problem to be solved: In view of the problems existing in the prior art such as the difficulty in controllable introduction of defects and large-scale supply during the preparation of oxygen-deficient materials, the complex preparation process and the safety risks, the present invention proposes an oxygen-deficient nanomaterial, a solid-phase molten zinc thermal reduction preparation method and application thereof. The preparation method is efficient, simple and universal, and adopts solvent-free solid-phase molten zinc thermal reduction technology to achieve the preparation of oxygen-deficient nanomaterials with adjustable oxygen defect concentration, which can be used for surface protection of aqueous zinc metal negative electrodes.

[0006] Technical solution: The first object of the present invention is to provide a solid phase molten zinc thermal reduction preparation method of oxygen defect nanomaterials, the steps are as follows:

[0007] Step 1: Mix the transition metal oxide nanomaterial with zinc powder, place the mixture in a ball mill, and add ball mill beads, wherein the mass ratio of zinc powder to transition metal oxide nanomaterial is 0.5% to 200%;

[0008] Step 2: Add dispersant to the ball mill, seal the ball mill, and perform ball milling. The ratio of dispersant to powder mixture is 0.5-10 mL / g.

[0009] Step 3, drying the ball-milled mixture to powderize it;

[0010] Step 4: placing the transition metal oxide nanomaterial / zinc powder mixture powder in a crucible, and heating and annealing in a tube furnace under a protective atmosphere for 0.5 to 5 hours, wherein the upper limit of the annealing temperature does not exceed the phase transition temperature of the prepared target defect oxide, which is determined by the species crystal form of the target defect oxide, and the lower limit needs to be higher than the melting point of the zinc powder;

[0011] Step 5: Treat the calcined product of the transition metal oxide nanomaterial / zinc powder mixture with a sufficient amount of 0.1-1.0 M dilute acid or dilute alkali, centrifuge the treated product, wash it with deionized water, and dry it to obtain the oxygen-deficient nanomaterial.

[0012] The present invention ball-mills the transition metal oxide material and the reducing agent zinc powder to mix well, then performs an inert annealing treatment, and then acid / alkali washes the final product to remove zinc and other impurities. The solid-phase molten zinc thermal reduction technology is innovatively proposed, and the oxygen-deficient nanomaterial with adjustable oxygen defect concentration is successfully prepared, which has important scientific significance, broad application prospects and economic value.

[0013] Preferably, the transition metal oxide nanomaterial in step 1 is TiO2, SnO2, ZrO2 or BaTiO3 powder material, and the corresponding oxygen-deficient TiO 2-x SnO 2-x 、ZrO 2-x or BaTiO 3-x Nanomaterials.

[0014] Preferably, in step one, the mass ratio of zinc powder to TiO2 powder material is 0.5% to 200%, the mass ratio of zinc powder to SnO2 powder material is 0.5% to 110%, the mass ratio of zinc powder to ZrO2 powder material is 0.5% to 130%, and the mass ratio of zinc powder to BaTiO3 powder material is 0.5% to 100%.

[0015] Preferably, the dispersant in step 2 is at least one of ethanol, isopropanol, N,N-dimethylformamide (DMF), acetonitrile and tetrahydrofuran (THF).

[0016] Preferably, the rotation speed of the ball milling treatment in step 2 is 200 to 600 rpm, the rotation direction is forward or a combination of forward and reverse rotations, and the ball milling time is 1 to 72 h.

[0017] Preferably, the protective atmosphere in step 4 is at least one of nitrogen (N2), argon (Ar) and helium (He).

[0018] Preferably, the annealing temperature in step 4 is 420-550°C.

[0019] Preferably, in step 5, the dilute acid is dilute hydrochloric acid, dilute sulfuric acid or dilute nitric acid, and the dilute alkali is dilute ammonia water, sodium hydroxide or potassium hydroxide solution.

[0020] Furthermore, in step five, zinc can be recovered and extracted by diluting the washing leachate, thereby realizing the recycling of the reducing agent.

[0021] The second object of the present invention is to provide an oxygen-deficient nanomaterial prepared based on the above method.

[0022] The third object of the present invention is to provide an application of the above oxygen-deficient nanomaterial as a negative electrode protective material for aqueous zinc ion batteries. The oxygen-deficient nanomaterial can be used as a negative electrode protective material for aqueous zinc ion batteries, and can effectively improve the cycle life of zinc batteries.

[0023] Beneficial effects: (1) The present invention provides a simple, controllable, universal and scalable mild solid-phase molten zinc thermal reduction technology for preparing oxygen-deficient nanomaterials. It uses environmentally friendly, low-cost zinc powder as a reducing agent, and uses solvent-free, mild and high-temperature zinc melting to infiltrate oxides to remove surface oxygen atoms for reduction. Electron paramagnetic resonance testing has verified that a series of defective nanomaterials with adjustable oxygen defect concentrations have been successfully prepared; and the prepared oxygen-deficient nanomaterials are used as protective materials for metal negative electrodes of zinc ion batteries, effectively improving the cycle life of zinc batteries.

[0024] (2) Compared with the existing commonly used oxygen-deficient material preparation technologies such as high-temperature hydrogen reduction, complex structure carbonization, solvent thermal reduction and other technologies (the controllable introduction of defects is difficult, the preparation process is complex and has safety risks), the solid-phase molten zinc thermal reduction technology reported in the present invention is used to prepare oxygen-deficient materials. It has a mild operating temperature, no special equipment requirements, and is compatible with existing industrial production technologies. It has good processing safety, industrial compatibility and production universality, and has broad application prospects and economic value.

[0025] (3) Zinc can be recovered and extracted by diluting the washing leachate, thereby realizing the recycling of the reducing agent.

[0026] (4) The defective oxide nanomaterials proposed in the present invention are also widely reported as excellent catalyst materials and can be used in related catalysis, energy storage and environmental science fields, and have important scientific significance and application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 For a series of zinc thermal reduction TiO 2-x XRD pattern of .

[0029] Figure 2 For a series of zinc thermal reduction TiO 2-x TEM images of the original TiO2 (a) and the reduced TiO2 (b) 2-x (10% Zn); c is reduced TiO 2-x (20% Zn); d is reduced TiO 2-x (30% Zn).

[0030] Figure 3 For a series of zinc thermal reduction TiO 2-x Room temperature EPR spectrum.

[0031] Figure 4 For zinc thermal reduction of TiO 2-x Room temperature EPR spectrum of the control experimental sample.

[0032] Figure 5 For zinc thermal reduction of SnO 2-x (20%Zn), ZrO 2-x (20% Zn) and BaTiO 3-x XRD spectrum of (20% Zn), in which a is zinc thermal reduction of SnO2-x ; b is zinc thermal reduction of ZrO 2-x ; c is zinc thermal reduction of BaTiO 3-x .

[0033] Figure 6 SEM images of SnO2, ZrO2 and BaTiO3 before and after zinc thermal reduction treatment. In the figure, a is the initial SnO2; b is the initial ZrO2; c is the initial BaTiO3; d is the zinc thermal reduction SnO 2-x ; e is zinc thermal reduction ZrO 2-x ; f is zinc thermal reduction of BaTiO 3-x .

[0034] Figure 7 For zinc thermal reduction of SnO 2-x (20%Zn), ZrO 2-x (20% Zn) and BaTiO 3-x Room temperature EPR spectrum of (20% Zn), in which a is zinc thermal reduction of SnO 2-x ; b is zinc thermal reduction of ZrO 2-x ; c is zinc thermal reduction of BaTiO 3-x .

[0035] Figure 8 For zinc thermal reduction of TiO 2-x Symmetrical battery with protected zinc metal anode at 1 mAh cm -2 Cyclic performance diagram under surface capacity conditions, in which a is TiO 2-x (30%Zn) protected zinc foil at 5mA cm -2 Under current density; b is TiO 2-x (30%Zn) Protective zinc foil at 20mAcm -2 Cycling performance under different current densities, using unprotected bare zinc foil as a comparison sample.

[0036] Fig. 9 For zinc thermal reduction of SnO 2-x 、ZrO 2-x and BaTiO 3-x Symmetrical cell with protected zinc anode at 20 mA cm -2 Current density and 1mAh cm -2 Cyclic performance diagram under surface capacity conditions, in which a is SnO 2-x (20% Zn) protective zinc foil; b is ZrO 2-x (20% Zn) protective zinc foil; c is BaTiO 3-x (20% Zn) Protective zinc foil. DETAILED DESCRIPTION

[0037] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0039] Unless otherwise specified, the raw materials used in the examples of this specification are all from common commercially available products.

[0040] Among them, zinc powder was purchased from Sinopharm Chemical Reagent Co., Ltd. with an initial particle size of 2-20 μm;

[0041] Anatase TiO2 powder was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with an initial particle size of ∼60 nm;

[0042] Tetragonal SnO2 powder was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with an initial particle size of 50-70 nm;

[0043] Monoclinic ZrO2 powder was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with an original particle size of ∼200 nm;

[0044] Tetragonal BaTiO3 powder was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with an original particle size of ∼0.3–3 μm;

[0045] The ball milling beads are agate ball milling beads with particle sizes of 5mm, 8mm and 10mm, and are used in a ratio of 2:1:1;

[0046] Zinc foil was purchased from Qinghe County Tengfeng Metal Materials Co., Ltd. with a thickness of 100 μm.

[0047] Example 1

[0048] This embodiment provides an oxygen-deficient TiO 2-x The preparation method of nanomaterials, the specific steps are as follows:

[0049] Weigh 2g of rutile TiO2 powder and 0.2g of zinc powder (or 0.4g, 0.6g of zinc powder), mix and place in a ball mill; add agate beads, then add 10mL of anhydrous ethanol, seal the ball mill, and rotate forward and reversely at 400rpm for 20h; place the ball milled product in an oven and dry it at 60℃ to obtain a TiO2 / zinc powder mixture. Mechanically powderize it, take an appropriate amount of TiO2 / zinc powder ball milling mixture and place it in a crucible, put it in a high-temperature tube furnace, and anneal it at 500℃ for 2h in a nitrogen atmosphere. Cool to room temperature, treat the annealed product with sufficient 0.5M dilute hydrochloric acid for 1h, centrifuge and wash it with deionized water 3 times, and dry it to obtain oxygen-deficient titanium dioxide nanomaterials, which are respectively recorded as TiO 2-x (10 / 20 / 30% Zn). Zinc can be recovered and extracted by diluting the washing leachate, thus realizing the recycling of the reducing agent.

[0050] A series of zinc-thermally reduced TiO 2-x The XRD pattern of Figure 1 As can be seen from the figure, compared with the initial anatase TiO2 powder (recorded as initial TiO2 (0% Zn)), the prepared products all maintain the anatase crystal phase structure, indicating that the zinc thermal reduction process does not change the nature of the material, ensuring that the prepared material maintains the target crystal form (the upper limit of the annealing temperature is determined according to the species crystal form of the target defect oxide prepared, and the lower limit is preferably not lower than the melting point of zinc powder).

[0051] A series of zinc-thermally reduced TiO 2-x TEM images of Figure 2 As can be seen from the figure, the obtained product still maintains the nanoparticle morphology of the initial TiO2 material, and no obvious secondary growth of particles and particle sintering and agglomeration occur.

[0052] A series of zinc-thermally reduced TiO 2-x The room temperature EPR (electron paramagnetic test) spectrum is shown in Figure 3 The results show that the initial TiO2 material has no obvious oxygen vacancy signal, while the zinc thermal reduction TiO 2-x The (10 / 20 / 30% Zn) material exhibits obvious oxygen vacancy signals, and the oxygen vacancy signals increase with the increase of the zinc reducing agent ratio, indicating that the oxygen defect concentration can be adjusted and controlled.

[0053] Comparative Example 1

[0054] The same as Example 1, except that no zinc powder is added, and no ball milling and pickling are performed.

[0055] The details are as follows: the initial rutile TiO2 powder is placed in a crucible, put into a high-temperature tube furnace, annealed at 500°C for 2 hours in a nitrogen atmosphere, and cooled to room temperature to obtain a direct inert annealed TiO2 material, recorded as annealed TiO2 only (0% Zn).

[0056] Comparative Example 2

[0057] Same as Example 1, except that no annealing treatment is performed.

[0058] The details are as follows: 2g of anatase TiO2 powder and 0.6g of zinc powder are weighed, mixed and placed in a ball mill; agate beads are added, and then 10mL of anhydrous ethanol is added, the ball mill is sealed, and the ball mill is rotated forward and reversely at 400rpm for 20h; the ball milled product is placed in an oven and dried at 60℃ to obtain a TiO2 / zinc powder mixture. It is mechanically powdered, treated with sufficient 0.5M dilute hydrochloric acid for 1h, centrifuged and washed with deionized water 3 times, and dried to obtain the product, which is recorded as ball-milled acid-washed TiO2 (30% Zn, unannealed).

[0059] Zinc-thermally reduced TiO prepared in Example 1 and Comparative Examples 1-2 2-x The room temperature EPR spectrum of the control experimental sample is shown in Figure 4 In Example 1, TiO is reduced by zinc heat 2-x (30% Zn) is used as a representative. It can be seen from the figure that in the absence of zinc powder, the same inert atmosphere annealing process cannot introduce oxygen defects into TiO2; in the case of zinc powder co-ball milling, direct pickling without annealing cannot introduce oxygen defects into TiO2. The above results show that both zinc powder reducing agent and temperature-controlled annealing process are indispensable. Solid-phase molten zinc thermal reduction is a complete process. Only by combining the two can TiO2 with adjustable and controllable oxygen defect concentration be prepared. 2-x Oxygen-deficient materials.

[0060] Example 2

[0061] This embodiment provides an oxygen-deficient SnO 2-x The preparation method of nanomaterials, the specific steps are as follows:

[0062] Weigh 2g of tetragonal SnO2 powder and 0.4g of zinc powder, mix and place in a ball mill; add agate beads, then add 10mL of anhydrous ethanol, seal the ball mill, and rotate forward and reversely at 400rpm for 20h; place the ball milled product in an oven and dry it at 60℃ to obtain a SnO2 / zinc powder mixture. Powder it, take an appropriate amount of SnO2 / zinc powder ball mill mixture and place it in a crucible, put it in a high-temperature tube furnace, and anneal it at 500℃ for 2h in a nitrogen atmosphere. Cool it to room temperature, treat the annealed product with sufficient 0.5M dilute hydrochloric acid for 1h, centrifuge it and wash it with deionized water 3 times, and dry it to obtain SnO2-x (20% Zn).

[0063] Example 3

[0064] This embodiment provides an oxygen-deficient ZrO 2-x The preparation method of nanomaterials, the specific steps are as follows:

[0065] Weigh 2g of monoclinic ZrO2 powder and 0.4g of zinc powder, mix and place in a ball mill; add agate beads, then add 10mL of anhydrous ethanol, seal the ball mill, and rotate forward and reversely at 400rpm for 20h; place the ball milled product in an oven and dry it at 60℃ to obtain a SnO2 / zinc powder mixture. Powder it, take an appropriate amount of ZrO2 / zinc powder ball mill mixture and place it in a crucible, put it in a high-temperature tube furnace, and anneal it at 500℃ for 2h in a nitrogen atmosphere. Cool it to room temperature, treat the annealed product with sufficient 0.5M dilute hydrochloric acid for 1h, centrifuge it and wash it with deionized water 3 times, and dry it to obtain ZrO 2-x (20% Zn).

[0066] Example 4

[0067] This embodiment provides an oxygen-deficient BaTiO 3-x The preparation method of nanomaterials, the specific steps are as follows:

[0068] Weigh 2g of tetragonal BaTiO3 powder and 0.4g of zinc powder, mix and place in a ball mill; add agate beads, then add 10mL of anhydrous ethanol, seal the ball mill, and rotate forward and reversely at 400rpm for 20h; place the ball milled product in an oven and dry it at 60℃ to obtain a SnO2 / zinc powder mixture. Powder it, take an appropriate amount of BaTiO3 / zinc powder ball mill mixture and place it in a crucible, put it in a high-temperature tube furnace, and anneal it at 500℃ for 2h in a nitrogen atmosphere. Cool it to room temperature, treat the annealed product with sufficient 0.5M dilute hydrochloric acid for 1h, centrifuge it and wash it with deionized water 3 times, and dry it to obtain BaTiO 3-x (20% Zn).

[0069] like Figure 5 As shown, SnO2, ZrO2 and BaTiO3 powders were subjected to zinc thermal reduction treatment, and the obtained products still maintained the crystal form of the original materials, and no obvious phase change was found.

[0070] The SEM images of the relevant zinc thermal reduction products prepared in Examples 2-4 are shown in Figure 6 , compared with the initial material, the heat treatment process did not cause obvious particle size growth, and the obtained product was nanoscale in size.

[0071] Furthermore, if Figure 7As shown, the room temperature electron paramagnetic test results of the products prepared in Examples 2-4 indicate that the solid phase molten zinc thermal reduction technology successfully introduced stable oxygen defect structures into SnO2, ZrO2 and BaTiO3 materials, proving the processing effectiveness and universality of this method.

[0072] Example 5

[0073] This embodiment provides an oxygen-deficient TiO 2-x The preparation method of nanomaterials, the specific steps are as follows:

[0074] Weigh 2g of rutile TiO2 powder and 4g of zinc powder, mix and place in a ball mill; add agate beads, then add 60mL of anhydrous ethanol, seal the ball mill, and rotate forward and reversely at 200rpm for 72h; place the ball milled product in an oven and dry it at 60℃ to obtain a TiO2 / zinc powder mixture. Mechanically powder it, take an appropriate amount of TiO2 / zinc powder ball milling mixture and place it in a crucible, put it in a high-temperature tube furnace, and anneal it at 420℃ in a nitrogen atmosphere for 0.5h. Cool to room temperature, treat the annealed product with sufficient 1M dilute hydrochloric acid for 1h, centrifuge and wash it with deionized water 3 times, and then dry it to obtain oxygen-deficient titanium dioxide nanomaterials.

[0075] Example 6

[0076] This embodiment provides an oxygen-deficient TiO 2-x The preparation method of nanomaterials, the specific steps are as follows:

[0077] Weigh 2g of rutile TiO2 powder and 0.01g of zinc powder, mix and place in a ball mill; add agate beads, then add 10mL of anhydrous ethanol, seal the ball mill, and rotate forward and reversely at 600rpm for 1h; place the ball-milled product in an oven and dry it at 60°C to obtain a TiO2 / zinc powder mixture. Mechanically powder it, take an appropriate amount of TiO2 / zinc powder ball-milled mixture and place it in a crucible, put it in a high-temperature tube furnace, and anneal it at 550°C for 5h in a nitrogen atmosphere. Cool to room temperature, treat the annealed product with sufficient 0.1M dilute hydrochloric acid for 1h, centrifuge and wash it with deionized water 3 times, and then dry it to obtain oxygen-deficient titanium dioxide nanomaterials. Application examples Application and effect verification:

[0078] The prepared oxygen-deficient nanomaterial (TiO 2-x (30%Zn), SnO 2-x (20%Zn), ZrO 2-x (20% Zn) or BaTiO 3-x(20% Zn)), conductive carbon black Super P and battery-grade polyvinylidene fluoride powder are mixed and ground evenly in a mass ratio of 8:1:1, dispersed in a methyl pyrrolidone solvent, the solvent to powder ratio is 1-10mL / g, and stirred to obtain an active material slurry. It is then coated on the surface of a commercial zinc foil, vacuum dried and punched to obtain a working electrode, which is used to assemble a Zn-Zn symmetrical battery (using 1mol / LZnSO4 aqueous electrolyte and glass fiber diaphragm). Subsequently, the battery is subjected to a constant current charge and discharge cycle test using a blue battery test system.

[0079] like Figure 8 As shown, compared with the bare zinc foil without surface modification, the oxygen defect TiO 2-x The zinc anode modified with (30% Zn) material can effectively improve the cycle stability and cycle life and reduce its potential polarization. -2 At 5 mA cm -2 and 20mAcm -2 At the current density of 1.544 W / m, the cycle life of the bare zinc foil symmetric battery is about 180 cycles and 325 cycles respectively, while the cycle life of the TiO 2-x The cycle lives of the (30% Zn) protected zinc foil symmetric cells are approximately 1320 cycles and 3950 cycles, respectively.

[0080] like Fig. 9 As shown, compared with the unprotected bare zinc foil, SnO 2-x (20%Zn), ZrO 2-x (20% Zn) and BaTiO 3-x (20% Zn) can also effectively improve the cycle stability and cycle life of the zinc electrode. -2 Current density and 1mAhcm -2 Under surface capacity, SnO 2-x (20%Zn), ZrO 2-x (20% Zn) and BaTiO 3-x The cycle life of the (20% Zn) protected zinc foil symmetric battery is approximately 1640 cycles, 2380 cycles and 775 cycles, respectively, proving the effectiveness of the oxygen defect material prepared by this method.

[0081] Oxygen-deficient TiO 2-x (30% Zn) has the most significant improvement on the cycle life of the zinc negative electrode. Preferably, it can be used as an ideal zinc negative electrode protection material.

[0082] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.

Claims

1. A method for preparing oxygen-deficient nanomaterials by solid-phase molten zinc thermal reduction, characterized in that: Here are the steps: Step 1: Mix the transition metal oxide nanomaterial with zinc powder, place the mixture in a ball mill, and add ball mill beads, wherein the mass ratio of zinc powder to transition metal oxide nanomaterial is 0.5% to 200%; Step 2: Add dispersant to the ball mill, seal the ball mill, and perform ball milling. The ratio of dispersant to powder mixture is 0.5-10 mL / g. Step 3, drying the ball-milled mixture to powderize it; Step 4: placing the transition metal oxide nanomaterial / zinc powder mixture powder in a crucible, and heating and annealing in a tube furnace under a protective atmosphere for 0.5 to 5 hours, wherein the upper limit of the annealing temperature does not exceed the phase transition temperature of the prepared target defect oxide, and the lower limit needs to be higher than the melting point of the zinc powder; Step 5: Treat the calcined product of the transition metal oxide nanomaterial / zinc powder mixture with a sufficient amount of 0.1-1.0 M dilute acid or dilute alkali, centrifuge the treated product, wash it with deionized water, and dry it to obtain the oxygen-deficient nanomaterial.

2. The method for preparing oxygen-deficient nanomaterials by solid-phase molten zinc thermal reduction according to claim 1, characterized in that: In step 1, the transition metal oxide nanomaterial is TiO2, SnO2, ZrO2 or BaTiO3 powder material, and in step 5, oxygen-deficient TiO is prepared accordingly. 2-x SnO 2-x 、ZrO 2-x or BaTiO 3-x Nanomaterials.

3. The method for preparing oxygen-deficient nanomaterials by solid-phase molten zinc thermal reduction according to claim 2, characterized in that: In step 1, the mass ratio of zinc powder to TiO2 powder material is 0.5% to 200%, the mass ratio of zinc powder to SnO2 powder material is 0.5% to 110%, the mass ratio of zinc powder to ZrO2 powder material is 0.5% to 130%, and the mass ratio of zinc powder to BaTiO3 powder material is 0.5% to 100%.

4. The method for preparing oxygen-deficient nanomaterials by solid-phase molten zinc thermal reduction according to claim 1, characterized in that: The dispersant in step 2 is at least one of ethanol, isopropanol, N,N-dimethylformamide, acetonitrile and tetrahydrofuran.

5. The method for preparing oxygen-deficient nanomaterials by solid-phase molten zinc thermal reduction according to claim 1, characterized in that: The rotation speed of the ball milling treatment in the step 2 is 200 to 600 rpm, the rotation direction is forward or a combination of forward and reverse rotations, and the ball milling time is 1 to 72 hours.

6. The method for preparing oxygen-deficient nanomaterials by solid-phase molten zinc thermal reduction according to claim 1, characterized in that: In the step 4, the protective atmosphere is at least one of nitrogen, argon and helium.

7. The method for preparing oxygen-deficient nanomaterials by solid-phase molten zinc thermal reduction according to claim 1, characterized in that: The annealing temperature in step 4 is 420-550°C.

8. The method for preparing oxygen-deficient nanomaterials by solid-phase molten zinc thermal reduction according to claim 1, characterized in that: In step 5, the dilute acid is dilute hydrochloric acid, dilute sulfuric acid or dilute nitric acid, and the dilute alkali is dilute ammonia water, sodium hydroxide or potassium hydroxide solution.

9. An oxygen-deficient nanomaterial prepared by the method according to any one of claims 1 to 8.

10. Use of the oxygen-deficient nanomaterial according to claim 9 as a negative electrode protective material for aqueous zinc ion batteries.

Citation Information

Patent Citations

  • Method for synchronous preparation of C3N4 and TiOxN2-x visible-light induced photocatalyst

    CN110280284A

  • High-dispersion ruthenium-modified oxygen-defect-rich semiconductor photocatalyst as well as preparation method and application thereof

    CN112403462A

  • Preparation method and application of zinc ion battery metal zinc negative electrode dynamic interface coating

    CN113540390A

  • Preparation method and application of porous hafnium zinc oxide negative electrode protection layer rich in oxygen vacancies

    CN117199356A

Cited By

  • ZnO / BTO composite catalyst and preparation and application methods thereof

    CN121571131A